The Application of Artificial Intelligence at Chinese Digital Platform Giants: Baidu, Alibaba and Tencent - Kai Jia; Martin Kenney; Juri Mattila; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2018)
The Chinese digital platform giants – Baidu, Alibaba and Tencent – have quickly risen to be amongst the most notable developers and users of artificial intelligence. One important catalyst for this development has been the so-called Platform Business Group (PBG) strategy used by Chinese digital platform firms. In this strategy a platform firm aims to develop powerful synergies by tightly linking together a number of different platforms it owns so as to offer multiple services to users under its umbrella. By applying the PBG strategy, Baidu, Alibaba, and Tencent are able to exploit enormous multi-faceted datasets on individuals for use in the development of artificial intelligence algorithms. As a result, the Chinese platform giants appear to be taking a somewhat different approach with the development and use of artificial intelligence than their Western counterparts. If the Chinese platform giants succeed in their efforts to expand into the global market, their business strategies will introduce a different threat to the conventional European industries from those challenges already presented by Apple, Amazon, Facebook, Google, and Microsoft.
Keywords: L8; L86; O3; O33; 330; Artificial Intelligence; Platforms; Platform Business Group strategy; Baidu; Alibaba; Tencent; Künstliche Intelligenz; Internetportal; E-Business; Strategisches Management; China